Nordic Council (2006)
The Nordic Council is the official governmental forum for Nordic co-operation. It consists of Denmark, Finland, Iceland, Norway, Sweden and the autonomous territories of the Faroe Islands, Greenland and Åland and covers a wide range of co-operation areas from legal and economic issues to education, culture and environment.